Public Satisfaction on Online Service Development: (Case Study: Bantulpedia Application) - Sukarno, Mohamad; Pribadi, Ulung (Universitas Negeri Semarang, 2023)
Purpose: This study analyzes public satisfaction with Bantulpedia Application users in Bantul Regency. The measurement was carried out using variables from the Online Service Index (OSI) framework consisting of institutional framework, service provision, content provision, technology, and e-participation.Methods: The research method used is quantitative, with the primary data source being a questionnaire totaling 100 respondents. SmartPLS 3 software is used in conducting data analysis for this research.Results: The research results show that variable institutional framework has a positive and significant influence on the satisfaction of Bantulpedia Application users. Meanwhile, the variables service provision, content provision, technology, and e-participation did not positively and significantly influence the satisfaction of Bantulpedia application users.Novelty: This study is unique by using OSI parameters by correlating them with application-based public satisfaction assessments (online services), which the majority of this theory is only used to measure e-government development and various aspects of it. This research contributes to providing a new perspective on using OSI theory in the realm of online services (applications) not only as a predictive measurement but as a significant research object (a country). In addition, the empirical contribution is to conduct a public satisfaction test on using the Bantulpedia Application. So that later it can also be adopted and provide space for other local governments to adopt OSI as an indicator of this online service.